2001
DOI: 10.1080/10420150108216917
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced effects in soda-lime silicate glasses of different origin

Abstract: 2001) Radiation-induced effects in soda-lime silicate glasses of different origin, Radiation Effects and Defects in Solids, 156:1-4, 353-358,Correlated measurements of optical absorption and thermoluminescence of g-irradiated sodalime silicate (SLS) glasses were performed to detect and characterize the induced radiation damage in these materials. Three kinds of hole-type defect centers have been distinguished in glasses which differ with respect to the content of the glass-network modifiers and some multivalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…The main observation in their study is the diffusion of alkali metals (Na and K) from soda-lime glass substrates into thin films of some metal oxides, which results in a less TL signal and a peak shift to higher temperature. Other TL and optical absorption measurements on glasses materials were also reported by Suszynska et al [9]. They observed broad glow peaks at around 473 K, which is similar to these obtained in the present materials.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The main observation in their study is the diffusion of alkali metals (Na and K) from soda-lime glass substrates into thin films of some metal oxides, which results in a less TL signal and a peak shift to higher temperature. Other TL and optical absorption measurements on glasses materials were also reported by Suszynska et al [9]. They observed broad glow peaks at around 473 K, which is similar to these obtained in the present materials.…”
Section: Discussionsupporting
confidence: 91%
“…A further increase in Na + and a decrease in Si 4+ concentrations could result in 473 K peak intensity quenching and enhancing the intensity of the peak at 643 K. This means that the access of Na + ions have acted as quenchers for the hole centres 'AlO 4 ' and enhanced the induced NBO, which are the defects responsible for the peak at 643 K (figures 4-6). Suszynska et al [9] have tried to correlate the optical absorption measurements and TL peaks in soda lime glasses. They found that Na-type glass (which could be identified by its brownish/greyish colour) has shown absorption maxima located at 624 and 419 nm and both bands are corresponding to the same type of defects, which are in agreement with the three peaks observed in TL (the strongest one is at around 473 K) of all samples although with different efficiencies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Eq. 10, τ 0 is the pre-exponential factor (typically ~13µs), k B is the Boltzmann's constant and E a the activation energy of the decay (~1 eV for silicate glasses [5,[7][8][9][10][11][12]).…”
Section: Modelingmentioning
confidence: 99%